2006
DOI: 10.1248/bpb.29.1202
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Effect of Main Components Kakkalide and Tectoridin of Puerariae Flos and Their Metabolites

Abstract: Most herbal medicines are orally administered as decoctions. The components of these herbal medicines are therefore inevitably brought into contact with intestinal microflora in the alimentary tract. Some components may be transformed by intestinal bacteria before absorption from the gastrointestinal tract. Studies on the metabolism of such components by human intestinal microflora are of great importance to understanding their biological effects. 1,2)The flower of Pueraria thunbergiana (family Leguminosae), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…1,2) In East Asia, this flower has also recently been used in herbal medicines for the management of menopausal symptoms. 4,5) Puerariae thomsonii is known to contain 7 isoflavones (4 isoflavone glucosides: tectoridin, tectorigenin 7-O-xylosylglucoside, 6-hydroxygenistein-6,7-diglucoside, and glycitin; and 3 aglycones: tectorigenin, glycitein, and genistein) and 3 saponins (soyasaponin I, kaikasaponin III, and kakkasaponin I). 6) It has been reported that isoflavones such as genistein affect lipid metabolism in the liver and inhibit adipocyte differentiation, 7,8) and that saponins have an inhibitory effect on lipase activity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) In East Asia, this flower has also recently been used in herbal medicines for the management of menopausal symptoms. 4,5) Puerariae thomsonii is known to contain 7 isoflavones (4 isoflavone glucosides: tectoridin, tectorigenin 7-O-xylosylglucoside, 6-hydroxygenistein-6,7-diglucoside, and glycitin; and 3 aglycones: tectorigenin, glycitein, and genistein) and 3 saponins (soyasaponin I, kaikasaponin III, and kakkasaponin I). 6) It has been reported that isoflavones such as genistein affect lipid metabolism in the liver and inhibit adipocyte differentiation, 7,8) and that saponins have an inhibitory effect on lipase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Ohwi, where kakkalide is a predominant isoflavone, and Pueraria thomsonii Benth, where tectoridin is a major isoflavone ). Pharmacologically, kakkalide, irisolidone-7-O-␤-D-xylopyranosyl-(136)-␤-D-glucopyranoside, shows a wide spectrum of bioactivities such as hepatoprotection (Yamazaki et al, 1997;Han et al, 2003;Lee et al, 2005a), estrogenic effect (Shin et al, 2006), anti-inflammation (Park et al, 2007), antihyperlipidemia (Min and Kim, 2007), antioxidation , and others. The major metabolite in the blood of rats orally given kakkalide was its aglycone irisolidone, but not kakkalide itself.…”
mentioning
confidence: 99%
“…Han et al (2003) isolated irisolidone and kakkalidone (irisolidone-7-O-␤-D-glucopyranoside) from an anaerobic medium containing kakkalide and human fecal bacteria, and they found that kakkalide exerts the protective activity against ethanol-induced mortality and hepatic injury in mice only by oral route. On the other hand, the activity of irisolidone was stronger than that of kakkalide whether it was given orally or intraperitoneally (Yamaki et al, 2002;Min and Kim, 2007;Shin et al, 2006). In addition, some isoflavone aglycone metabolites such as tectorigenin, glycitein, and genistein showed more potent activity than their glycoside precursors (Yamaki et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ohwi. In China, P. flos was traditionally used to treat diabetes mellitus and alcoholic intoxication because of its activities including antioxidant, 17 detoxification of alcohol, 18 hepatoprotective 19 and anticancer. 20 The aqueous extract of P. flos contained various isoflavonoids and triterpenoid saponins possessing pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%